Imaging girls: visual methodologies and messages for girls' education - Magno, Cathryn; Kirk, Jackie (Compare, 2008)
This article describes the use of visual methodologies to examine images of girls used by development agencies to portray and promote their work in girls' education, and provides a detailed discussion of three report cover images. It details the processes of methodology and tool development for the visual analysis and presents initial 'readings' of the selected images. This initial study highlights the relevance of image analysis to the field of gender, education and development and of critical reflection on the different messages and meanings inherent in images of girls and girls' education which relate to complex questions of power and privilege, position and post-coloniality. The authors recommend that within development agencies education and communication specialists work together to develop more sophisticated processes for image selection, review and feedback, and that researchers in the field further engage with visual methodologies to inform current theories of girlhood, education, schooling and empowerment.
Keywords: Education; Girls; Images; Methodology; Representation; dept.edl